Examination of duodenal and colonic microbiome changes in mouse models of acute and chronic pancreatitis - Rabea Lange; Juliane Glaubitz; Fabian Frost; Andreas Geisz; Ali A. Aghdassi; F. Ulrich Weiss; Matthias Sendler (Scientific Reports)
Abstract The exocrine pancreas is the main source of digestive enzymes which are released from secretory vesicles of acinar cells into the small intestine. Enzymes, including amylases, proteases and lipases, degrade the ingested food and thus determine the nutritional substrate for the gut microbiota. Acute (AP) and chronic pancreatitis (CP) are associated with a transitional or progressive exocrine pancreatic dysfunction, we analysed in the present study how an experimental induction of pancreatitis in mouse models affects the colonic and duodenal microbiome composition. Evaluation by 16 S rRNA gene sequencing revealed specific microbiome changes in colonic as well as in duodenal samples in different models of AP and CP. Mild acute pancreatitis, which is associated with a transient impairment of pancreatic secretion showed only minor changes in microbial composition, comparable to the ones seen in progressive dysfunctional mouse models of CP. The strongest changes were observed in a mouse model of severe AP, which suggest a direct effect of the immune response on gut microbiome in addition to a pancreatic dysfunction. Our data indicate that highly dysbiotic microbiome changes during pancreatitis are more associated with the inflammatory reaction than with a disturbed pancreatic secretion.